IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DILIHAT DARI ASPEK KOMUNIKASI DI DESA SUPUT KECAMATAN HARUAI KABUPATEN TABALONG - Muhamad Rasyad; Rahmi Hayati (p3m.stiatabalong.ac.id, 2022)
Implementation of the Non-Cash Food Assistance Program (Bpnt) From a Communication Aspect in Suput Village, Haruai Sub-district, Tabalong Regency. Non-Cash Food Assistance (BPNT) is a program that aims to reduce the expenditure burden of KPM (Beneficiary Families) through fulfilling food needs, providing more balanced nutrition to KPM (Beneficiary Families), increasing target accuracy and timing of receiving food assistance for KPM (Beneficiary Families), giving more choices and control to KPM (Beneficiary Families) in meeting food needs and encouraging the achievement of sustainable development goals (Sustainable Development Goals/SDGs). The purpose of this study was to find out and analyze the Implementation of the Non-Cash Food Assistance Program (BPNT) from a Communication Aspect in Suput Village, Haruai District, Tabalong Regency. This research uses a type of qualitative descriptive approach, the data collection methods used are observation, interviews, and documentation. The data analysis used is the Miles and Hubberman model. The results showed that the Non-Cash Food Assistance Program (BPNT) seen from the communication aspect on the transmission indicator was categorized as highly implemented, on aspects categorized as quite implemented, and on the consistency indicator it was categorized as quite implemented so that the conclusion of the research was the Non-Cash Food Assistance Program (BPNT) seen from the aspect of communication in the village of Suput it is categorized as implemented. Keywords: Implementation, BPNT, Communication Aspects